A Case of an Asymptomatic Woman After a Fracture Repair. Issue 7 (July 2022) - Kupchik, Nicole; Green, Joel
Abstract : Editor's note: This is the next installment in a series on electrocardiogram (ECG) interpretation. Nurses in all settings should know the basics, as medications and physiological changes can cause cardiac arrhythmias. Each article will start with a brief case scenario and an ECG strip and then take you step by step through analyzing the heart rhythm. Abstract : This latest article in a series on the basics of electrocardiography (ECG) interpretation presents a case scenario and an ECG strip and takes readers step by step through analyzing the heart rhythm.